2021
DOI: 10.3389/fonc.2021.736597
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Mechanisms Involved in Endocrine Resistance

Abstract: Endocrine therapy is a standard treatment offered to patients with ERα (estrogen receptor α)-positive breast cancer. In endocrine therapy, ERα is either directly targeted by anti-estrogens or indirectly by aromatase inhibitors which cause estrogen deficiency. Resistance to these drugs (endocrine resistance) compromises the efficiency of this treatment and requires additional measures. Endocrine resistance is often caused by deregulation of the PI3K/AKT/mTOR pathway and/or cyclin-dependent kinase 4 and 6 activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 258 publications
(336 reference statements)
1
10
0
Order By: Relevance
“…And one resistance mechanism upstream of the signaling pathways and growth factor receptors is increased expression of receptor ligands, such as heregulin [24,25,28]. In our studies we also observed the inactivation of STAT3 and STAT5, and enhanced STAT3 signaling has been linked to the development of estrogen resistance [26]. Collectively, our data demonstrate that GZ17-6.02 and palbociclib interact through multiple individual mechanisms to reduce cell viability.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…And one resistance mechanism upstream of the signaling pathways and growth factor receptors is increased expression of receptor ligands, such as heregulin [24,25,28]. In our studies we also observed the inactivation of STAT3 and STAT5, and enhanced STAT3 signaling has been linked to the development of estrogen resistance [26]. Collectively, our data demonstrate that GZ17-6.02 and palbociclib interact through multiple individual mechanisms to reduce cell viability.…”
Section: Discussionsupporting
confidence: 66%
“…Loss of ER function will play a role reduced growth and in reduced viability [19]. ER+ mammary carcinoma cells have been shown to develop resistance to direct ER inhibitors through several mechanisms, most notably through activation of PI3K-AKT and MEK1/2-ERK1/2 signaling [22][23][24][25][26][27][28][29]. And one resistance mechanism upstream of the signaling pathways and growth factor receptors is increased expression of receptor ligands, such as heregulin [24,25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Such phosphorylations can be triggered by receptor tyrosine kinases (RTKs) through the PI3K/AKT/mTOR/p70S6K and the Ras/Raf/MEK1/ERK1/2 pathways. Endocrine resistance, the resistance to endocrine therapy, is often caused by permanent activation of RTKs ( 35 37 ). Of the RTKs, IGF1R is of particular importance for ERα-dependent transcription.…”
Section: Estrogen Receptor αmentioning
confidence: 99%
“…In recent years, many new classes of antitumour compounds with a significant effect on the signalling pathways in tumour cells have been developed [1][2][3][4][5][6]. Along with the new classes, antihormonal drugs-SERMs (selective oestrogen receptor modulators) and SERDs (selective oestrogen receptor degraders)-remain highly relevant as an antitumour therapy [7][8][9]. Hormone therapy [10][11][12][13][14] is one of the most common types of treatment of hormone-dependent tumours including breast cancer, ovarian cancer, endometrial and prostate tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Ten years of tamoxifen treatment reduced the incidence of breast cancer recurrence by more than 25%, compared with 5 years of tamoxifen treatment [24]. Despite the high effectiveness of tamoxifen, the problem of resistance to this drug is especially urgent [7,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%